Independent living, emotional well-being, and quality of life in people with disabilities: the mediator role of self-determination and satisfaction with participation - Cegarra, Blanca; Cattaneo, Gabriele; Ribes, Alina; Solana-Sánchez, Javier; Saurí, Joan (Frontiers in Psychology, 2023)
Background. In the field of disability and rehabilitation, participation in society has become an important therapeutic objective due to its potential impact on rehabilitation, prognosis, and patient’s mid and long-term well-being. However, only a few studies have explored this issue in relation with the subjective perspective of individuals with disabilities about their decision-making capacity and satisfaction with the activities in which they participate. Objective. Our aim is to analyze the relationship between participation in society of people with disabilities and both emotional well-being and quality of life, including variables about subjective perspective of participation (satisfaction) and the ability to decide and pursue their own preferences. Method. The cross-sectional study presented here includes 424 participants with disabilities over 18-years-old from Spain. This research is part of a larger ongoing longitudinal cohort study called Participa (https://participa.guttmann.com/en/). Participants were asked to complete several on-line surveys to explore quality of life, emotional well-being, participation in society, self-determination, and independent living. Results. The results revealed an association between the dimensions of participation satisfaction, self-determination, and levels of independent living with both quality of life and emotional well-being. Mediation models indicated that satisfaction and self-determination partially mediated the relationship between independent living and both quality of life and emotional well-being. Conclusions. The level of independent living, self-determination, and satisfaction with participation are fundamental aspects for promoting a high quality of life and emotional well-being in people with disabilities. These findings carry significant implications for health and social services, as well as policies guidelines, highlighting the need to prioritize empowerment and self-determination in all interventions designed for people with disabilities.